Detection of Insertion Sequence ISAba1 Among Clinical Isolates of Carbapenems-Resistant Acinetobacter baumannii - Saad Laiby Hamed (College of Pharmacy / Mustansiriyah University, 2014)
Acinetobacter baumannii is an opportunistic pathogen with increasing clinical importance, especially in immunocompromised patients, causing nosocomial infections of the lungs, urinary tract and surgical wounds. Carbapenems are important antibiotics for treating multidrug resistant A. baumannii infections. Insertion sequence ISAba1 has been detected in correlation with many antimicrobial agent resistance genes in A. baumannii. The aim of this study was to investigate existence of insertion sequence (ISAba1) in clinical isolates of carbapenem-resistant A. baumannii isolated from hospitals in Baghdad city. Seventy Acinetobacter baumannii isolates were obtained from clinical samples (42 from sputa and 28 from blood) between September 2012 and March 2013.Antibiogram towards several groups of antimicrobial agents including: β- Lactams; aminoglycosides; fluoroquinolone ; and sulfa; as well as the combination of amoxicillin / β-Lactamase inhibitor using disc diffusion method was carried out. Multi-drug resistant isolates were observed in almost all the studied isolates .Minimum inhibitory concentration values were demonstrated using agar dilution method for imipenem antibiotic. Forty eight (68.57%) of 70 isolates were resistant to imipenem with values of MIC ranging between (16-256) μg/ml.ISAba1 sequence among imipenem resistant isolates using PCR technique were identified in 44 isolates (91.66%). Sequencing of amplified product (549 bp) was performed to ensure the occurrence of the ISAba1 sequence in the studied carbapenem-resistant A.baumannii